The safety and efficacy of mesenchymal stromal cells in ARDS: a meta-analysis of randomized controlled trials - Fengyun Wang; Yiming Li; Bingqing Wang; Jianguo Li; Zhiyong Peng (Critical Care, 2023)
Abstract Mesenchymal stromal cells (MSC) have shown potential efficacy in both animal and human trials of acute respiratory distress syndrome (ARDS). Especially during the COVID-19 pandemic, MSC was intensely studied for treating COVID-19-induced ARDS. The purpose of this study is to evaluate the safety and efficacy of MSC in ARDS via a meta-analysis of randomized controlled trials (RCTs). Therefore, a meta-analysis of RCTs of MSC as a therapy for ARDS was conducted. The protocol of this review was registered on Open Science Framework. With no language restriction and according to the “PICOs” principle, searches were conducted on Pubmed and Embase to retrieve any clinical literature on MSC for ARDS. Any RCT, which compared MSC to controls for ARDS, where MSC and controls were intravenously infused, of any dosage, was eligible for inclusion. A total of 13 RCTs, which evaluated MSC versus control for treating ARDS, enrolling a total of 655 cases, met the inclusion criteria and appeared in this meta-analysis. A heterogeneity assessment was carried out using the χ 2 test, where a P value less than 0.05 was considered significant. The choice of a fixed-effect or a random-effect model was decided by the I 2 value in each of the analyses. This meta-analysis indicated that there was no significant difference in terms of adverse events between MSC and control for ARDS (OR = 0.64, 95% CI [0.34, 1.20], P = 0.17, and I 2 = 0%). In comparison with control, MSC could reduce the mortality of ARDS (OR = 0.66, 95% CI [0.46, 0.96], P = 0.03, and I 2 = 10%). Based on the results of our meta-analysis, the safety of MSC was demonstrated to be non-inferior to that of standard treatment, and MSC may reduce the mortality rate of ARDS. Though the heterogeneity in the main results was low (I 2 < 25%), more high-quality and large-scale clinical trials are needed to further confirm our findings.